Multivalent manganese complex decorated amphiphilic dextran micelles as sensitive MRI probes1. Issue 8 (28th February 2015) - Wu, Changqiang; Li, Danyang; Yang, Li; Lin, Bingbing; Zhang, Houbing; Xu, Ye; Cheng, Zhuzhong; Xia, Chunchao; Gong, Qiyong; Song, Bin; Ai, Hua
<x xml:space="preserve">Abstract</x> Manganese complex decorated amphiphilic dextran micelles were prepared and have a high T1 relaxivity in MRI.